Clinical features and natural course of Behcet's disease in 661 cases: a multicentre study - Alpsoy, E.; Donmez, L.; Onder, M.; Gunasti, S.; Usta, A.; Karincaoglu, Y.; Akman, A. (Wiley-Blackwell Publishing, Inc, 2007)
Background Behcet's disease (BD) is a systemic inflammatory disease with unpredictable exacerbations and remissions. The natural course of BD is not fully known. Objectives We aimed retrospectively to determine the occurrence of the symptoms in chronological order. We also evaluated the influence of the treatment and follow-up on the clinical severity and tried to identify the factors determining severe organ involvement. Methods Six hundred and sixty-one patients were involved in this multicentre study. The symptoms of the disease were recorded retrospectively in the time order of the manifestations in each patient. Results Oral ulcers were the most common manifestation (100%), followed by genital ulcers (85.3%), papulopustular lesions (55.4%), erythema nodosum (44.2%), skin pathergy reaction (37.8%), and articular (33.4%) and ocular involvement (29.2%). Oral ulcers were the most common onset manifestation (88.7%). The mean +/- SD duration between the onset symptom and the fulfilment of diagnostic criteria was calculated to be 4.3 +/- 5.7 years. The clinical severity score was significantly increased in the noncompliant treatment group compared with the compliant group with the passage of time (P < 0.001). The frequency of ocular involvement and genital ulcers was significantly higher in patients whose disease onset was at < 40 years. Genital ulcers, ocular involvement, papulopustular lesions, thrombophlebitis and skin pathergy reaction were found to be significantly more frequent in males. Conclusions Mucocutaneous lesions are the hallmarks of the disease, and especially oral ulcers precede other manifestations. The increase in clinical severity score is more pronounced in patients without regular treatment and follow-up. Male sex and a younger age at onset are associated with more severe disease.
Keywords: Behcet's disease; chronology; mucocutaneous symptoms; natural course; onset manifestation